Genome destabilization-associated phenotypes arising as a consequence of therapeutic treatment are suppressed by Olaparib - Suzuki, Mafuka; Fujimori, Haruka; Wakatsuki, Kakeru; Manaka, Yuya; Asai, Haruka; Hyodo, Mai; Matsuno, Yusuke; Kusumoto-Matsuo, Rika; Shiroishi, Mitsunori; Yoshioka, Ken-ichi (PLOS ONE, 2023)
Malignancy is often associated with therapeutic resistance and metastasis, usually arising after therapeutic treatment. These include radio- and chemo-therapies, which cause cancer cell death by inducing DNA double strand breaks (DSBs). However, it is still unclear how resistance to these DSBs is induced and whether it can be suppressed. Here, we show that DSBs induced by camptothecin (CPT) and radiation jeopardize genome stability in surviving cancer cells, ultimately leading to the development of resistance. Further, we show that cytosolic DNA, accumulating as a consequence of genomic destabilization, leads to increased cGAS/STING-pathway activation and, ultimately, increased cell migration, a precursor of metastasis. Interestingly, these genomic destabilization-associated phenotypes were suppressed by the PARP inhibitor Olaparib. Recognition of DSBs by Rad51 and genomic destabilization were largely reduced by Olaparib, while the DNA damage response and cancer cell death were effectively increased. Thus, Olaparib decreases the risk of therapeutic resistance and cell migration of cells that survive radio- and CPT-treatments.